A comparative analysis of the effective and local slip lengths for liquid flows over a trapped nanobubble. (July 2018) - Hu, Haibao; Wang, Dezheng; Ren, Feng; Bao, Luyao; Priezjev, Nikolai V.; Wen, Jun
Highlights: The study reports the results of molecular dynamics simulations of slip flows over smooth surfaces with nanobubbles trapped by the wettability step. The spatial distribution of the local and effective slip lengths at surface of the nanobubble is analyzed. The dependence of slip length on the gas areal fraction, shear rate, pinned and continuous interfaces are studied in the manuscript. Abstract: The gas–liquid interfaces distributed on a superhydrophobic (SHP) surface promote the effective slip and might result in significant drag reduction desirable in many applications. While the slippage of water past gas–liquid interfaces on structured SHP surfaces has attracted wide attention, the slip behavior at gas–liquid interfaces trapped by the wettability step still remains unclear. Using molecular dynamics simulations, we first demonstrated that the three-phase contact line can be pinned on a smooth substrate of mixed wettability. We then numerically investigated slip flows over smooth surfaces with flattened gas bubbles trapped by the wettability step. It was found that the local slip length is relatively large at the gas–liquid interface and its spatial distribution becomes asymmetric due to shear-induced deformation of the attached bubble, while the effective slip length remains nearly constant. With increasing gas areal fraction, the local and effective slip lengths become larger, especially in the case of a stripe-like continuous gas–liquid interface where the interface curvature in the flow direction is absent.